Makna Deiksis dalam Puisi Bithoqoh Huwiyah Karya Mahmoud Darwish: Kajian Pragmatik - Azza Shofia Rahmada; Abdul Muntaqim Al Anshory (PRASASTI: Journal of Linguistics, 2025)
Mahmoud Darwish's poem Bithoqoh Huwiyah reflects the Palestinian people's struggle to maintain their identity amidst the prolonged conflict with Israel. This research departs from the main question: how deixis elements in this poem, such as the use of the words "I", "you", and references to place and time, are able to represent the collective experience of the Palestinian people. This research aims to dig deeper into how deixis elements form meanings that are closely related to the socio-political context. By using descriptive qualitative method, data were collected through reading and note-taking techniques, then analyzed using Milles and Huberman's model. The results of the analysis show that persona deixis in this poem does not solely refer to the poet as an individual, but symbolizes the collective voice of the Palestinian people. Meanwhile, the deixis of place and time emphasizes the attachment of the Palestinian people to their lost homeland and the long struggle they face. This study also confirms that language in literature can be a powerful tool to voice resistance to injustice, build solidarity, and strengthen collective identity in socio-political struggles.